Земля камбарская, родная: История Камбарки / А. Новиков - Новиков А. (1957)
Экземпляры: КР (20010118) / Инвентарный номер: у51748 / Цена: 15.00 / Сис.шифр: 63.3(2Р-6У) / Авт.знак: Н 73 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)